Plant microRNAs: Biogenesis, Homeostasis, and Degradation - Wang, Junli; Mei, Jun; Ren, Guodong (Frontiers in Plant Science, 2019)
MicroRNAs (miRNAs), a class of endogenous tiny non-coding RNAs, are master regulators of gene expression among most eukaryotes. The abundances of intracellular miRNAs are orchestrated and under multiple levels of control, including transcription, processing, RNA modification, RNA induced silencing complex (RISC) assembly, miRNA-target interaction, as well as turnover. In this review, we summarize our current understanding of molecular components and mechanisms that influence miRNA biogenesis, homeostasis and degradation in plants. We also make comparisons with findings from other organisms where necessary.